The effectiveness of a program based on multiple intelligences in developing the creative expression skills of outstanding students at the secondary level in Sana’a, the capital, Sana’a - Almnswory, Mohammed AbdulAllah (Journal of Curriculum and Teaching Methodology, 2023)
The study aimed to reveal the effectiveness of a proposed program based on multiple intelligences in developing creative expression skills among outstanding first-year secondary students in the capital city for the academic year 2021-2022 AD. The experimental approach was used based on the design of the experimental and control groups. Creative expression, as well as the design of an achievement test in the field of creative expression skills prepared by the researcher, and the tools were applied to a sample of students from Gamal Abdel Nasser School for the Outstanding, which was chosen intentionally as it is the only school for the outstanding in the capital Sana’a, where two divisions were selected from the first grade secondary students from The origin of (6) people, and they were chosen randomly, the number of the sample was (52) students, representing 26% of the size of the original community of (200) students. The research sample was divided into two experimental and control groups, with (26) students for each group. There are seven types of intelligences (linguistic, logical, visual, musical, kinesthetic, social, and personal). The study reached several results, including: The students of the experimental group excelled in the post application (testing creative expression skills) at the level of each domain, and at the level of each of the sub-skills separately, as there were statistically significant differences at the level of.05 between the mean scores of the experimental and control groups in the test of creative expression skills in Post application in favor of the experimental group.